Faktor Tata Kelola dan Lingkungan yang Mempengaruhi Malnutrisi Berat di Indonesia: Bukti untuk Memperkuat Program Makan Gratis yang Bergizi - Muhammad Abduh; Aos Kuswandi; Derriansya Putra Jaya (Jurnal Bina Praja, 2026)
Indonesia’s Free Nutritious Meal Program (Makan Bergizi Gratis, MBG), mandated under Presidential Regulation No. 115/2025, is designed to reduce child malnutrition through decentralized implementation. This study examines whether village governance readiness and environmental degradation are associated with severe malnutrition events, which are rare but operationally important for program targeting. Villages are used as the unit of analysis because they are the primary frontline setting for coordination, community monitoring, service responsiveness, and environmental exposure. Using administrative data from 2,876 villages, the study estimates event occurrence using a logit model and event burden using a negative binomial model. The stable negative binomial count model, retained after fuller specifications showed convergence and collinearity problems, indicates that governance readiness is positively associated with severe malnutrition burden but not statistically significant, whereas environmental conditions, service support, and poverty remain relevant to interpretation and targeting. These findings support a risk-informed MBG strategy that integrates service readiness, social vulnerability, and environmental conditions rather than relying solely on reported cases.